2001
DOI: 10.1055/s-2001-10620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silymarin on the Acute Stage of the Trinitrobenzenesulphonic Acid Model of Rat Colitis

Abstract: The intestinal anti-inflammatory activity of several doses of silymarin was tested in the acute stage of the trinitrobenzenesulfonic acid (TNBS) model of rat colitis. The results obtained show that oral pre-treatment with 50 mg/kg of silymarin significantly attenuated macroscopic colonic damage as well as reduced colonic myeloperoxidase activity compared to non-treated colitic animals. The beneficial effect was accompanied by an improvement in the colonic oxidative status, which was altered in colonic inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
4
15
0
1
Order By: Relevance
“…The incidence of side effects is very low and they are mostly limited to some gastrointestinal symptoms like bloating and dyspepsia [25]. Supporting the present data, silymarin has been found to have positive effects in the acute stage of a rat model of colitis in comparison to sulfasalazine [53], when tested in doses different to the present doses and measuring other biomarkers like colonic glutathione.…”
Section: Discussionsupporting
confidence: 71%
“…The incidence of side effects is very low and they are mostly limited to some gastrointestinal symptoms like bloating and dyspepsia [25]. Supporting the present data, silymarin has been found to have positive effects in the acute stage of a rat model of colitis in comparison to sulfasalazine [53], when tested in doses different to the present doses and measuring other biomarkers like colonic glutathione.…”
Section: Discussionsupporting
confidence: 71%
“…23) Moreover, the colonic tissue AP activity has been used to differentiate Crohn's disease from ulcerative colitis, because their AP enzymatic activity to be higher than Crohn's disease. 31) In the present study it was observed a higher AP activity in the colon from colitic animals compared to the non-colitic animals from acute intestinal inflammation model induced by TNBS/ ethanol, as well as demonstrated by Cruz et al 32) The intestinal anti-inflammatory effect of coumarin (5, 50 mg/kg), 4-hydroxycoumarin (5, 10, 25 mg/kg) and sulphasalazine (25 mg/kg) was evidenced also by the significant reduction of the AP enzymatic activity compared to control animals.…”
Section: Discussionsupporting
confidence: 54%
“…Several poliphenolic compounds, particularly flavonoids, also shown non dose-dependent response in TNBS model of rat colitis, probably due to produce in lower doses antioxidant effects and higher doses pro-oxidant effects. 13,37,[40][41][42] In addition, several phenols have a dual effect on prostaglandin H synthase, with low concentrations stimulating and high concentrations inhibiting this enzyme. 43) Phenols stimulate prostaglandin H synthase by acting as reducing substrates for the oxidized intermediates of prostaglandin biosynthesis, thereby accelerating the peroxidase cycle and by functioning as electron-donating cosubstrates for the peroxidase component of prostaglandin synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed preclinical and clinical evidence from previous studies support this possibility [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Future studies, should concentrate on which specific silymarin component(s) are most effective in other relevant pre-clinical models of IBD [10].…”
Section: Resultsmentioning
confidence: 92%